ECR e o consumidor: um estudo sobre o comportamento do consumidor, em relação aos valores ofertados por ECR - Ramuski, Carmen Lidia (2004)
This study investigates the existences of differences in the consumer behavior related to ECR values. The main objective of the study is to analyze if the same group of consumers attribute different importer to ECR values, with or without price, and if theses differences were related with socials status. Three hundred self-administrate questionnaires where collect in São .Paulo city focusing two categories of grocery goods. The main results of the study were: a) there were differences in the behavior of the consumers not only in relation with product categories but also related to the importance of the ECR value; b) differences in the consumer behavior related between social classes; c) Different groups of consumer emerged when ECR value were considered. d) Price represents a significant attribute to consumer.